2023
DOI: 10.3390/vaccines11010143
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Attitudes toward Influenza Vaccination: A Behaviour and Social Drivers Survey

Abstract: This study aimed to understand the intention and correlation of receiving and recommending influenza vaccine (IV) among healthcare workers (HCWs) in China during the 2022/2023 season using the behavior and social drivers (BeSD) tools. A self-administered electronic survey collected 17,832 participants on a media platform. We investigated the willingness of IV and used multivariate logistic regression analysis to explore its associated factors. The average scores of the 3Cs’ model were compared by multiple comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For the 2022–2023 season a recent study from China, (17,832 healthcare workers), showed by multivariate logistic regression analysis that 74.89% participants were willing to receive influenza vaccine and 82.58% of them were willing to recommend [ 57 ]. This is far from our results, where in the 582 HCW group of responders, only 158 (27.14%) HCW vaccinated each year for flu, and 276 (47.42%) HCW did not vaccinate at all.…”
Section: Discussionmentioning
confidence: 99%
“…For the 2022–2023 season a recent study from China, (17,832 healthcare workers), showed by multivariate logistic regression analysis that 74.89% participants were willing to receive influenza vaccine and 82.58% of them were willing to recommend [ 57 ]. This is far from our results, where in the 582 HCW group of responders, only 158 (27.14%) HCW vaccinated each year for flu, and 276 (47.42%) HCW did not vaccinate at all.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we can observe that some of the main reasons for rejecting vaccination are as follows: the lack of a sense of influenza risk and the belief that the flu is not a severe illness [2,27,34,[38][39][40][41], concerns about side effects [27,32,[34][35][36][37][40][41][42][43], distrust of vaccine safety [22,32,34,35,37,39], doubts about vaccine efficacy [27,32,34,35,37,39,40], considering it unnecessary [32], self-perception as a healthy population [22,27,36], and workload as a barrier to either accessing vaccination points or a lack of time [27,32,39,44].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that political bodies and public health organizations present specific initiatives to increase confidence in vaccines and launch public vaccination campaigns raising awareness about the importance of vaccination and their safety, taking into account sociocultural factors. Otherwise, they could have a negative influence on vaccination coverage [38,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Development and pilot testing of a structured and closed-ended questionnaire started in June 2021, and ethical clearance for the study was obtained. The questionnaire was adapted from the behavioral and social drivers of vaccination model of the World Health Organization (WHO) and was available in English and Somali [13][14][15]. It was tested on a group of health workers to determine its clarity and applicability.…”
Section: Data Collectionmentioning
confidence: 99%